Soluble recombinant CR2 (CD21) inhibits Epstein-Barr virus infection. - Nemerow, G R (1990)
Epstein-Barr virus (EBV), an oncogenic herpesvirus of humans, displays selective tropism for B lymphocytes and epithelial cells. EBV tropism is thought to be determined in part by a unique host cell receptor termed CR2 (CD21). Although previous studies have demonstrated that CR2 mediates EBV binding to B cells, its role in initiating EBV infection and B-cell transformation is less certain. In the studies reported here, soluble recombinant CR2 was shown to cause substantial inhibition of EBV infection of B cells in vitro, indicating that CR2 binding initiates EBV infection. Soluble CR2 may represent a therapeutic agent for acute and chronic EBV infections in humans.